Sustainable supply chain management in the route for a circular economy: An integrative literature review - Jorge Alfredo Cerqueira-Streit; Gustavo Yuho Endo; Patricia Guarnieri; Luciano Batista (Logistics, 2021)
Background: Sustainable supply chain management (SSCM) considers social, environmental, and economic dimensions of sustainability. In the context of the pandemic, organizations must face consequences striking the wider dimensions of sustainability. Thus, after the COVID-19 pandemic, how will the value chains collaborate for the transition from a traditional (linear) to a Circular Economy? Methods: From this question, in this paper, we analyze the international papers that connect sustainable supply chain management (SSCM) with circular economy (CE).We conducted an Integrative Literature Review based on the Web of Science and Scopus databases from 2010 to 2020, using the Methodi Ordinatio protocol to classify the papers. Results: The 37 best-ranked papers were analyzed thoroughly. The results show the prominent authors, institutions, the network relationship between authors, the evolution of publications, and the leading journals. The content of these articles was categorized and discussed about the changes in the way products are manufactured, distributed, consumed, and recovered. The integration of CE principles in SSCM has been evaluated as having potential utility for industries, cities, and businesses in general. Conclusions: Finally, an agenda was identified with suggestions for further research, which can aid researchers and practitioners acting in this field. Managers can obtain insights to improve supply chain sustainability and consequently respond to the challenges imposed by the current pandemic.
Keywords: 650; circular economy; integrative literature review; sustainable supply chain management